Jieduquyuziyin prescription promotes the efficacy of prednisone via upregulating Nrf2 in MRL/lpr kidneys. (15th November 2022) - Du, Lijun; Feng, Yuxiang; Wang, Chenxi; Shi, Xiaowei; Wen, Chengping; He, Zhixing; Zhang, Yun
Abstract: Ethnopharmacological relevance: The Jieduquyuziyin prescription (JP), a traditional Chinese medicine (TCM) formula, has been used as an approved hospital prescription to improve the efficacy of prednisone (Pred) in systemic lupus erythematosus (SLE) and lupus nephritis (LN) treatment. Although the synergistic effect of JP and Pred is prominent, the underlying mechanisms require further investigation. Aim of the study: To explore the key therapeutic targets of JP in improving the role of Pred in the treatment of LN. Materials and methods: Lupus-prone female MRL/ lpr mice were administered JP, Pred, or JP combined with Pred. The effect of JP on LN was estimated by evaluating renal function and inflammation levels in the kidneys. On this basis, RNA sequencing of kidney tissues was performed, and the differentially expressed genes were analyzed and summarized. The role of JP in the expression of nuclear factor erythroid 2-related factor 2 (NFE2L2 or Nrf2) in the kidneys was further confirmed by real-time PCR, immunohistochemistry, and western blotting. Results: JP combined with Pred exhibited the most remarkable therapeutic effect compared with JP or Pred alone. Transcriptome analysis indicated that Nrf2, a central mediator of the antioxidative response, was significantly upregulated by JP. Based on these results, we speculated that Nrf2 is a critical factor for JP, improving the efficacy of Pred in treating LN by notably suppressing the oxidative stress level in the kidneys. Furthermore, we found that Nrf2 expression decreased with the exacerbation of LN in MRL/ lpr mice. In addition, the downregulated Nrf2 was notably restored after JP treatment, accompanied by suppressed oxidative stress levels in the kidneys. It includes inhibited accumulation of reactive oxygen species (ROS) and malondialdehyde (MDA), restored mitochondrial membrane potential (MMP) levels, and increased antioxidant enzyme activity of superoxide dismutase (SOD). Conclusions: Our findings show that JP increases Pred efficacy by increasing Nrf2 expression, implying that Nrf2 may be a promising therapeutic target for the treatment of LN. Graphical abstract: Image 1